Dispersion and frequency: Is there any difference as regards their relation to L2 vocabulary gains? - Alcaraz-Mármol, Gema (International Journal of English Studies, 2015)
Despite the current importance given to L2 vocabulary acquisition in the last two decades, considerable deficiencies are found in L2 students’ vocabulary size. One of the aspects that may influence vocabulary learning is word frequency. However, scholars warn that frequency may lead to wrong conclusions if the way words are distributed is ignored. That is to say, it seems that not only the number of occurrences (frequency) might affect L2 vocabulary acquisition, but also the way occurrences are distributed (distribution). This relationship between these two factors is represented by the so-called Gries’ index, known as dispersion. The present study aims to find out whether dispersion is more an accurate and reliable predictor for L2 vocabulary learning than frequency only.